Effect of concrete mixture components, proportioning, and compressive strength on fracture parameters. (10th May 2019) - Shafiei Dastgerdi, Aref; Peterman, Robert J.; Riding, Kyle; Beck, B. Terry
Highlights: Angularity and coarseness of aggregate has been shown to increase fracture toughness by up to 25% at low strengths. Lowering W/C ratio from 0.38 to 0.28 improves the fracture toughness by 30% at low strengths. Change in aggregate and proportioning of concrete is more effective at lower strengths. Abstract: Splitting cracks in pre-tensioned concrete members often occur at the early stages after detensioning. To prevent these splitting failures, concrete members need to be resistant to crack growth at the strengths in which the beam is detensioned. In this paper, the effect of different concrete parameters including aggregate shape and content, water-to-cementitious (w/c) ratio, fly ash, paste and air void content on the crack resistance of concrete used in concrete railroad ties were investigated using Two-Parameter Model (TPM). For each mixture evaluated, twelve three-point prisms were tested at 27.5, 41.3 and 55.1 MPa concrete compressive strengths (4000, 6000 and 8000 psi) to determine the effect of concrete compressive strength on crack growth potential. In addition, splitting tensile tests were conducted on three samples at each compressive strength for all mixtures. Finally, the results were analyzed and the function of utilized method was discussed. The results show that increasing angularity, aggregate size and volume, and decreasing w/c ratio improve fracture toughness by 30% whereas changing paste, fly ash and air void content negligibly influence fracture toughness. However, all improving factors were seen to be most effective at low strengths. The obtained fracture toughness values from this study could lead to a significant improvement of splitting crack resistance in pre-stressed concrete members where high amount of transverse stress is often introduced at low compressive strengths.